Albanian Minority questions in Macedonia– Selected Issues - Sielska, Zuzanna Halina (Political Preferences, 2018)
In the article I tried to select the most important issues and events related to the Albanian minority question in Macedonia. In the very beginning I explain the origin of the name Macedonia, the location of Macedonia and roughly summarize its way to independence in the 90's. Then I elucidate where the Albanian minority in Macedonia came from and why the conflict in Tetovo broke out. At the and I try to chronologically describe the events from 2001 that had impact on today's political situation in the state with special regard to the political crisis that lasted from 2014 to the implementation of the law guaranteeing Albanian as the second official language in Macedonia. Key words: Macedonia, Albanian minority, identity, conflict